Control interno de la cuenta proveedores de la empresa Agricola Briones Barragan Agribba S.A. periodo 2019 - Litardo Ortiz, Jhostin Javier (2020)
The company is located in the problem of action with the suppliers in full of the execution and control processes through the accounting accounts, the sales processes and the recruitment that they have as customers compared to the suppliers, unlike the year 2018 with 2019 it was possible to analyze the agreement between the two parties, performing at risk the work mechanism called "PROMPT PAYMENT". In 2018 the economic issue at the national level was better in all economic activities, in 2019 production was low, for this reason the companies also wanted to reach their margin, since they had already invoiced the product without it arriving yet. the merchandise and thus be able to receive it little by little in 2020 One of the accounts that is considered important within a company dedicated to agricultural commercial activity is the supplier account, since this allows knowing each of the debts and accounts that it presents an institution with a third party, in other words, the relationship that exists with the organizations that provide supplies or merchandise. To respond to the need to improve the way in which the company is carrying out an accounting process for the movements of its accounts payable, the same as by not having a process that is highly structured for internal control that allows direct proper management of your accounts with suppliers. The method that was used in this type of research was the descriptive method, which allowed us to describe each of the shortcomings that this institution carries, in addition to conducting a bibliographic research on topics related to the present case study.